Groundwater salinization in Graciosa and Pico islands (Azores archipelago, Portugal): processes and impacts - Andrade, C. (2020)
The overall groundwater chemistry is mainly controlled by Cl and Na, which account respectively for 10.4%–46.9% and 16%–39.7% of the relative major-ion content. Mean electrical conductivity (EC) in Graciosa is in the range 308 − 3462 μS/cm, while hand-dug wells in Pico are highly mineralized (1758–9732 μS/cm). Drilled wells in Pico are in the range of 186 μS/cm to 5625 μS/cm. Besides mixture with seawater, groundwater chemistry is also influenced by dissolution of silicate minerals which also contributes to water composition. Moreover, 18O and 2H stable isotope data show that a few samples depict an evaporative effect, resulting in heavier isotopic compositions besides mixing with a marine source. About 70% of the wells in Graciosa and Pico exceed the 200 mg Cl/L and the EC Portuguese reference values, severely constraining water supply. The impact on water quality is also shown by exceedances of the groundwater threshold values derived for the Azores River Basin District (89%).